Pengembangan Jurusan/Program Studi dalam Perspektif Universitas Islam Negeri (UIN) - Muhaimin Muhaimin (UIN Maulana Malik Ibrahim Malang, 2000)
Islamic education is an effort to develop an Islamic view of life, to be manifested in life and life skills (manual and mental-social) in harmony with their interests, talents, abilities and areas of expertise. the development of STAIN towards UIN seeks to capture ibrah, values, attitudes and ways of thinking and behaving scholars (scientists) in the classical period mentioned above, because it is considered capable of facing increasing and complicated challenges, caused by the rapid progress of science and technology . As an implication, the Islamic education system built and developed through UIN is expected to produce a rational and professional cleric; broad-minded; virtuous noble character; his knowledge is not limited to